Why leave the classroom? How field trips to the church affect cognitive learning outcomes. (February 2016) - Riegel, Ulrich; Kindermann, Katharina
Abstract: In religious education field trips to the church are regarded as powerful instructional instruments to improve students' competencies as they enable authentic contact with lived religion. We conceptualize the church building as an out-of-school learning environment following the Contextual Model of Learning (Falk & Dierking, 2000) and thereby reveal the chances of and barriers to knowledge gain here. We test this in a non-equivalent groups design with a pretest and posttest for four different groups using a dichotomous Rasch-model. A difference-in-difference regression analysis shows that field trips do better than classroom-teaching, but only if they enable the students to become familiar with the location. This is especially true for students with little to no religious education in their family. This article is the first to present data on learning outcomes in an out-of-school learning setting in religious education and the findings add to the relevant theories about field trips. Highlights: We compare cognitive learning outcomes inside and outside the classroom. We use difference-in-difference estimation with individual fixed-effects. The effects of field trips to the church depend on the position in the curriculum. It is important to familiarize the students with an unknown learning environment. This is especially true for those who lack religious education at home.